(untitled) (Al-Qamar, 2024)
This research paper explores the role of Orientalists in Islamic authorship and studies. It delves into the historical context of Orientalist contributions, examining their motivations, methodologies, and the impact of their works on Islamic scholarship. By analyzing the contributions of key figures in the field, the study assesses how Orientalists have influenced both Western and Islamic perceptions of Islamic history, theology, and culture. The paper also critically examines the controversies and debates surrounding Orientalist scholarship, particularly in terms of biases and representations. Through a comprehensive review of primary and secondary sources, this study aims to provide a nuanced understanding of the Orientalist role in the development and dissemination of Islamic knowledge.